New food technologies for food formulation - Martínez Monzó, Xavier (2025)
This module covers the theoretical background on the application of new food technologies for food formulation. It is a part of the the Blended Intensive Program (BIP): Food Innovation and the Consumer funded by Erasmus+ and developed within an international consortium, participated by: Universidade Aberta, UAb, Portugal (Coordinator Institution); Universitat Politècnica de València, UPV, Spain; Faculty of Sciences, University of Porto, Portugal, National and Kapodistrian University of Athens, UoA, Greece. The BIP Food Innovation and the Consumer is developed in the context of the e-learning mode under the UAb Lifelong Learning Unit Organization, and is a 3 ECTS program.